A Phenomenon of English Content Tiktok Videos as a Resource in Learning English Vocabulary - Linda Muflihah; Naf’an Tarihoran; Eulis Rahmawati (Journal of English Language Teaching and Cultural Studies, 2024)
The study aims to analyze the phenomenon of English Content TikTok Videos and explore students’ ways of English vocabulary at SMP Negeri 1 Gunungsari in academic year 2022/2023. The research question is how students’ perceptions in are developing their English vocabulary, what challenges do students face and how do they get vocabulary from the TikTok videos that have been watched. There are a lot of students who watching video TikTok without see a benefits from it, and finally the researcher make a decision to take the title in above. This study used Mixed Methods for different from previous research, Mixed methods is combine between quantitative and qualitative data. The instruments used in this study were questionnaires and semi-structured interviews. The research subjects were students of SMP Negeri 1 Gunungsari, for quantitative data collection, 116 students used snowball sampling, while for qualitative data convenience, 12 students were selected who had filled out the questionnaire. The research findings show their English vocabulary develops because of watching the videos. However, they also note that using TikTok videos can create problems due to network instability and low quotas. it was also found that students were able to increase their vocabulary because TikTok provided short videos with simple explanations, various themes and topics, and the ability to see subtitles for English vocabulary. The researcher concluded that TikTok videos had a significant effect on students' English vocabulary learning at SMP Negeri 1 Gunungsari. The researchers give an advice for another researcher to can develop how to take benefits from TikTok and can be refer this research to reference.